ONE-YEAR RETROSPECTIVE STUDY OF WILDLIFE MORBIDITY AND MORTALITY AT A VETERINARY CLINIC IN MINAS GERAIS, BRAZIL - Souza de Oliveira, Lucas Belchior; Magalhães Cunha , Maria da Consolação; Vaz de Melo, Maria Iabel (Revista de Ciência Veterinária e Saúde Pública, 2022)
Epidemiological data from a morbidity and mortality profile allows decision-making, a tool that can be applied in conservation medicine practices. Our objective was to trace an epidemiological profile of wildlife animals hospitalized in a veterinary clinic in Belo Horizonte, Minas Gerais, Brazil. Hospitalization and medical care data were collected from the animals from July 2015 to July 2016. It was recorded 639 animals, of which 66.5% (425) were birds, 28.17% (180) were mammals, and 5, 33% (34) were reptiles. Neonatal and pediatric care were the main comorbidity for birds and mammals, while for reptiles, the primary reason was for changes in specific systems. Overall mortality in the period was 33.6 per 100 animals, with higher rates (46% of deaths) from September to November. It was possible to observe for the most commonly hospitalized mammals, the biggest casualties of the disease were neonatal and young animals care and non-vehicular trauma. For birds, there was a direct relationship between receiving some species and neonatal and pediatric care. Our findings were similar to other researches carried out in different situations, but addressing wildlife casuistry. We concluded that, in our research context, birds were the most received group, followed by mammals, mainly associated with pediatric care, and then reptiles, associated with specific systems affections. It is suggested to standardize the data collection of wildlife admission in the primary care settings, allowing decision-making strategies for conservation medicine.